Mental preparation of olympic and paralympic swimmers: performance-related cognitions and emotions, and the techniques used to manage them - Saint-Martin, S. V.; nTurner, M. J.; nRuiz, M. C. (Journal of Physical Education and Sport, 2020)
Purpose: The present study investigated the cognitions and emotions of swimmers,and explored thepsychological techniques they use to manage these internal processesprior to and during their best and worst performances. Method: Seven Paralympic and five Olympic male Brazilian swimmers took part in this qualitative study. A semi-structured interview with open-ended questions was conducted to explore how swimmers interpreted and experienced specific competitive events and what they did to manage their internal processes, prior to and during what they considered to be their best and worst performances. The process of data analysis included inductiveand deductive approaches. Cognitive therapy theory wasused to establish some of the themes and sub-themes, also to contribute to the data analysis.Results: Functional cognitions and pleasant emotions were more commonly reported by swimmers associated to their best performances, whilst dysfunctional cognitions and unpleasant emotions were more common in their worst performances, both influenced by their beliefs about the preparation during the season.Swimmers used imagery, breathing, music, self-talk, and cognitive restructuring to manage their cognitions and emotions, mainly in the day of their best performances. Although swimmers believed that cognitions and emotions could influence their performances, they reporteddifficulty identifying, evaluating, and modifyingtheir dysfunctional thinking. Conclusion:Our findings suggest that different patterns of cognitions and emotions were related to swimmers` best and worst performances, which were influenced by their beliefs about the preparation during the season.These results support the use of individualized and task-specific mental preparation programsto help athletes identify and manage dysfunctionalcognitions and emotions, and elicitadaptive behaviors.